Perinatal Loss and Pregnancy Termination: Vulnerabily and Obstetric Violence - Josefina Goberna-Tricas; Sara Fernández-Basanta; Sergio Ramos-Pozón; Anna Falcó-Pegueroles (Universitat de Barcelona, 2024)
Spontaneous pregnancy loss is relatively common, although the exact prevalence of these losses is difficult to estimate. Women may also choose to abort. The current Spanish Organic Law 1/2023, of February 28, on sexual and reproductive health and voluntary pregnancy termination allows abortion by the woman's free and voluntary decision up to the 14th week of gestation. Additionally, up to the 22nd week, termination can be performed for medical reasons, such as fetal malformation or danger to the mother's life. Nowadays, pregnancies are intensely thought out and planned before they become a reality. Therefore, spontaneous pregnancy loss has significant meaning for the woman and her partner, who may feel vulnerable. For healthcare professionals, maintaining an appropriate psychological and moral environment to care for these women and their families is not always easy. Sometimes, professionals are not able to provide the necessary care for a variety of reasons, leading to cases of obstetric violence. If vulnerability is considered alongside other anthropological elements of medicine itself, such as co-responsibility or solidarity-thus understanding medicine beyond mere technique-we arrive at a bioethical approach where the ethics of care and responsibility become key to providing proper healthcare in these situations.